Reliability of passive lower limb flexibility in rugby sevens players measured with a new hand held dynamometer: A pilot study - Reeves, J.; Hume, P.; Wenham, M. (ISBS - Conference Proceedings Archive (Konstanz), 2012)
This study assessed the within-day reliability of five passive lower extremity flexibility measures using a unique hand held dynamometer (HHD) that simultaneously detects dynamic force applied via a force pad and alteration in orientation in space between start and end points of range of motion via a tilt sensor. Hip extensor flexibility in the passive straight leg raise, hip internal and external rotation and hip flexion in two Modified Thomas test positions were conducted on 21 elite male athletes from a rugby sevens training squad using the HHD. There was very good to excellent within-day reliability for the flexibility measures ICC 0.79-0.96 and standardised typical error 0.21-0.48. The HHD facilitated a consistent applied force across trials for each player helping to provide high within-day reliability for the flexibility measures.